Scenario simulation analysis of urbanization spatial pattern optimization promoting regional coordinated development: A case study of Guizhou, China - Yuzhu Meng; Mingyue Wang; Shu Shang; Zhenlong Hao (PLoS ONE, 2025)
This research delves into the optimization of urbanization spatial patterns in Guizhou Province, China. The findings reveal that with regional coordinated development as the central objective and the optimization of urbanization spatial patterns as the strategic focus, a research framework encompassing “temporal and spatial evolution of urbanization - identification and summation of pain points and difficulties - scenario simulation and optimization - strategic goal selection” is utilized to specifically tackle issues pertaining to urbanization spatial patterns. Through the construction of diverse scenarios and rigorous research analysis, an implementation pathway is derived, advocating for “strengthening the central region of Guizhou, fostering urban agglomeration development, reinforcing developmental support points, and promoting regional coordinated development.” This pathway is then applied to the optimization of urbanization spatial patterns in Guizhou. The study proposes the establishment of a “one body with two wings” urbanization spatial pattern, with Guiyang as the primary core and Zunyi, Liupanshui, Bijie, Anshun, Duyun, and Kaili serving as support points for Guizhou’s primary development zone. Furthermore, urban clusters centered on Xingyi in southwestern Guizhou and Tongren in northeastern Guizhou are projected to gradually emerge. The remaining regions will undergo coordinated development, ultimately contributing to the realization of overall regional coordinated development.